2008
DOI: 10.1016/j.neuroimage.2007.10.003
|View full text |Cite
|
Sign up to set email alerts
|

fMRI–EEG integrated cortical source imaging by use of time-variant spatial constraints

Abstract: In response to the need of establishing a high-resolution spatiotemporal neuroimaging technique, tremendous efforts have been focused on developing multimodal strategies that combine the complementary advantages of high-spatial-resolution functional magnetic resonance imaging (fMRI) and high-temporal-resolution electroencephalography (EEG) or magnetoencephalography (MEG). A critical challenge to the fMRI-EEG/MEG integration lies in the spatial mismatches between fMRI activations and instantaneous electrical so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
79
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 87 publications
(83 citation statements)
references
References 66 publications
(108 reference statements)
3
79
1
Order By: Relevance
“…The presence of a significant spatial correspondence is concordant with the fact that event-related electrical activity originates from the same areas for which a heamodynamic response is detected, and with the fact that the EEG and BOLD signals, although very different, are both representative of local synaptic activity (Liu and He 2008). Finding a significant spatial correspondence despite the very different spatial and temporal resolutions of the two modalities is a prerequisite for their direct integration, enabling to combine the high spatial resolution of fMRI with the high temporal resolution of ERPs.…”
Section: Resultssupporting
confidence: 70%
See 2 more Smart Citations
“…The presence of a significant spatial correspondence is concordant with the fact that event-related electrical activity originates from the same areas for which a heamodynamic response is detected, and with the fact that the EEG and BOLD signals, although very different, are both representative of local synaptic activity (Liu and He 2008). Finding a significant spatial correspondence despite the very different spatial and temporal resolutions of the two modalities is a prerequisite for their direct integration, enabling to combine the high spatial resolution of fMRI with the high temporal resolution of ERPs.…”
Section: Resultssupporting
confidence: 70%
“…In a recent article, it was demonstrated that the amplitude of the BOLD response can be predicted using a linear model based on the time-integral of the power of local event-related synaptic activity (Liu and He 2008). Complete correspondence, however, is not expected.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, Laplacian transformed data emphasize more cortical activities and suppress contributions from deep brain structures. Further research can be extended to estimating the cortical current density or volume current density distribution from the scalp EEG (Liu and He, 2008) by solving the inverse problem, and then applying the network measures, which would allow for a stronger inference of the inter-regional connectivity in the source domain. Such approaches could also be combined with inverse approaches better suited to modeling deeper sources such as the ACC.…”
Section: Discussionmentioning
confidence: 99%
“…Source space projection can be done with commonly used software packages (e.g., the open-source Matlab toolbox FieldTrip or BrainStorm or the commercial products BrainVoyager or Besa) by inverting a forward solution on the basis of given source dipole positions and orientations and a volume conductor model; all of the above can be individually estimated from anatomical MRI data of subjects (Chan et al, 2009 He and Liu, 2008;Liu and He, 2008;Michel et al, 2004;Pascual-Marqui, 1999)]. …”
Section: The Advantage Of Operating In Source Spacementioning
confidence: 99%